Analysis of ISO26262 standard application in development of steer-by-wire systems - Marchanka, Aliaksandr (My University, 2012)
Software for automotive industry has to be as reliable as it is reasonably possible avoid human and property hazard, caused by its failure. That is why industry is constantly producing software development standards, which capture the best practices, recommendations and state-of-the art development technologies. Hence companies are constantly challenged by the need to align their current development processes with the upcoming standards like ISO 26262 standard. This work aims to perform the comparative analysis of the processes applied in regard to the software development, as implemented in a specific project. Besides the analysis, as a result of this work, a tool to support Fault Tree Analysis has been developed. Fault Tree Analysis is recommended by the ISO26262 standard and a tool that implements it can significantly decrease the amount of effort required to produce safe and reliable software according to ISO26262.
Keywords: Data- och informationsvetenskap; Computer and Information Science